Study of the Anodic Dissolution Solutions of Single Crystals of Molybdenum Diselenide (MoSe2) in KOH Media - Sani, Ousmane Mahamane; Bougouma, Moussa; Abdoulkadri, Ayouba Mahamane; Ibrahim, Natatou; Legma, Jean Boukary (European Journal of Applied Sciences, 2022)
This work is a contribution to the study of semiconductor materials that are used in semiconductor electrolyte junctions for the conversion of light energy into electrical energy. The study was carried out in KOH medium on single crystals of molybdenum diselenide obtained by physical vapor transport and previously characterized by different analysis techniques (SEM, XRD, etc.). A preliminary study on standard molybdate ion solutions was first carried out in order to establish the potential domain of molybdate ions. Cyclic anodic redissolution voltammetry was used for the analysis of standard solutions and MoSe2 dissolving solutions obtained by anodic attack at fixed potential. The results obtained show a reduction peak towards -0.812V indicating the deposit during the pre-electrolysis. A first oxidation peak at around -0.740V and a secondary peak at around -0.429V corresponding to the oxidation of the deposit during redissolution. Analysis of the results shows that MoSe2 is not stable in KOH media.